Spesifikasi Kebutuhan Perangkat Lunak Sistem Informasi Penjaringan Kesehatan Siswa Sekolah Dasar - Putu Dian Karmana; Martya Rahmaniati Makful; Artha Prabawa (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
School-age children are candidates for the next generation, so to produce superior next generations, efforts are needed to maintain the health of students. One of the efforts made is through health screening activities for students carried out by schools through UKS/M with assistance from the local Puskesmas as an institution under the district/city Health Office. The results of this health screening activity must be reported and followed up quickly so that if there are cases of certain diseases in students, they can be handled immediately. However, in practice, there are still many obstacles to this activity, mainly caused by paper-based data management. Therefore, information system technology is needed so that the data management becomes better. Based on this, the author wishes to design a software requirement for elementary school students' health screening information system as an initial step in designing a web-based application that can be used by the puskesmas in managing health screening data for students in elementary schools. Based on the evaluation by the evaluator, this design requirement only accommodates 65% of the needs of prospective users. Therefore it is necessary to carry out further development to produce prototype designs with a higher percentage to produce web-based applications that suit the needs.